2018
DOI: 10.1111/gfs.12402
|View full text |Cite
|
Sign up to set email alerts
|

Winter grazing stockpiled native warm‐season grasses in the Southeastern United States

Abstract: In the Southeastern United States, native warm‐season grasses (NWSG) are not harvested during autumn to rebuild root reserves, resulting in de facto stockpiled winter forage. Senesced NWSG forage is considered nutritionally inadequate by temperate livestock managers, but comparable forage is regularly utilized in rangeland systems. This experiment compared the forage characteristics of two NWSG pastures: switchgrass [Panicum virgatum L. (SG)] and a two species mixture of big bluestem/indiangrass [Andropogon ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Temperatures were also slightly to well-above average for most months during the native grass growing season (about March through October at this location). Tilhou et al [6] reported that native tall prairie PWSG (e.g., Panicum virgatum, Adropogon gerardii, Sorghastrum nutans) were fully dormant in the upper humid, subtropical USA by late September. Temperatures after triticale planting each year (Table 2) were sufficiently warm to promote germination and growth of winter cereal forages [18], and irrigation was applied as needed throughout the winter cereal growing season to further promote growth [19].…”
Section: Weathermentioning
confidence: 99%
See 3 more Smart Citations
“…Temperatures were also slightly to well-above average for most months during the native grass growing season (about March through October at this location). Tilhou et al [6] reported that native tall prairie PWSG (e.g., Panicum virgatum, Adropogon gerardii, Sorghastrum nutans) were fully dormant in the upper humid, subtropical USA by late September. Temperatures after triticale planting each year (Table 2) were sufficiently warm to promote germination and growth of winter cereal forages [18], and irrigation was applied as needed throughout the winter cereal growing season to further promote growth [19].…”
Section: Weathermentioning
confidence: 99%
“…Options for grazing in semiarid, subtropical environments include native grasses (predominantly actively growing or dormant perennial warm-season grasses, PWSG), winter cereals and other annual or perennial cool-or warm-season domesticated pastures, crop residues, and grain crops [1,5]. During their period of active growth from spring through summer, native PWSG can provide Agronomy 2022, 12, 545 2 of 11 adequate nutrition for growing cattle [6]. Native PWSG also are available for grazing after they become dormant in autumn; however, plant maturity and weathering reduce their nutritive value, making them nutritionally inadequate to support most classes of livestock, especially in regard to crude protein (CP) [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The journal has seen a marked increase in the number of submissions of papers describing the science of warm-season grass systems, both in traditional tropical environments and in more temperate environments. These papers have encompassed the continuum of native and naturalized pastures (Tilhou et al, 2019), breeding and selection (de Fig ueiredo et al, 2019), agronomy (Boschma et al, 2019;Ruolo et al, 2019;Silva et al, 2019) and beef (Euclides et al, 2019) and dairy (Lima et al, 2019) production systems. This trend is likely to continue as we explore the complementarity of temperate and warm-season forages under changing climatic conditions.…”
Section: Warm-season Grassesmentioning
confidence: 99%